ISOLASI DAN KARAKTERISASI BAKTERI PELARUT POSFAT DARI BINTIL AKAR DAN RIZOSFIR PUTRI MALU (Mimosa pudica) DARI LAHAN PERTANIAN PENEDAGANDOR LOMBOK TIMUR - Nufus, Novita Hidayatun; Azhari, Anjar Pranggawan; Zubaidi, Akhmad; Dewi, Suprayanti Martia (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
The use of phosphate-solubilizing microbes derived from symbiotic or rhizosphere bacteria provides a solution to enhance the phosphate content for plants. The Mimosa pudica plant has been recognized for its rich population of beneficial microorganisms on its rhizophere and root nodules. A study was conducted to identify phosphate-solubilizing bacteria from the root nodules of Mimosa pudica, which were isolated from the Penedegandor East Lombok coastal region. The results showed that 4 out of 14 bacterial isolates from the root nodule and rhizosphere of Mimosa pudica (Isolate BA1, BA2, BA4, and T10) exhibited phosphate solubilizing activity. Isolate BA4 exhibited the highest solubilizing activity, as evidenced by a clear zone diameter of 24 mm, which was greater than the other isolates. This was followed by isolate BA2 with a clear zone diameter of 18 mm, isolate T10 with a clear zone diameter of 17 mm, and isolate BA1 with a clear zone diameter of 15 mm. The isolates were identified through colony visualization and morphological analysis as belonging to the genera Bacillus (BA2), Pseudomonas (Ba4), and Micrococcus (T10); however, the identity of the BA1 isolate could not be determined.